Experimental Study on Concrete With Partial Replacement of Coarse Aggregate with Cashew Shells. Issue 1 (March 2021) - Priyadharshini, B; Nirmala, R; Eshanthini,; Manoj Kumaar, C
Abstract: Concrete is a mix of cement, fine aggregate and coarse aggregate with water in correct proportion. Many attempts had been to replace the fine aggregate, coarse aggregate and cement in concrete. In this row replacement of coarse aggregate by cashew shells was tried. Over 66% of the overall country export cashew kernels. The cashew seeds is well acclaimed for its good quality and appearance. Concrete cubes and beams had casted using cashew shell as a partial replacement of the coarse aggregate in the proportion of 10%, 20% and 30% replacement. the specific gravity of the shell was analyzed and 16mm shell were selected for the experiment. The characteristic of concrete was determined and the result showed that 10% replacement of shell with coarse aggregate gives the optimum strength.